Learning Using Discussion Methods: An Effective Approach in Increasing Student Activity and Understanding - Euis Latipah; Fadia Salsabila; Mayangsari Mayangsari; Nyimas Dinar Misik (Madrasah Al-Wathoniyah : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
The discussion method is a learning strategy that encourages active involvement of students in exchanging ideas, engaging in dialogue, and collectively solving problems. This approach is proven effective in developing critical thinking skills, communication abilities, and broadening students’ knowledge. In the context of Islamic Religious Education (PAI) as well as other subjects, the discussion method plays a crucial role in character building, moral value instillation, and boosting students’ self-confidence. The implementation process includes selecting topics, dividing groups, group discussions, presenting results, and joint reflection. Although it has many advantages, this method also faces challenges such as domination by certain participants, limited time, and the need for teachers to possess special facilitation skills. To optimize its effectiveness, strategies such as role assignment within groups, thorough material preparation, effective time management, and teacher training are necessary. Therefore, the discussion method is a highly effective learning approach to enhance the quality of the learning process and holistic character development, especially in the context of PAI learning.